HUBUNGAN ANTARA HASIL BELAJAR SISWA PADA MATA PELAJARAN AQIDAH AKHLAK DALAM MATERI AYO KITA HORMATI ORANG TUA DENGAN SIKAP BIRRUL WALIDAIN KELAS X DI MAN 1 KETAPANG - Mutmainnah (Pascasarjana Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2019)
This study aims to determine: (1) student learning outcomes in the subject of Aqidah Akhlak in the subject Come on Respect for Our Parents with the birrul walidain attitude of class X students at MAN 1 Ketapang. (2) the attitude of Birrul Walidain to class X students at MAN 1 Ketapang. (3) how big is the relationship between student learning outcomes in the subject of Aqidah Akhlak in the material Come on Respect for Our Parents with the attitude of Birrul Walidain in class X students in MAN 1 Ketapang